Language Policy of the Soviet State and its Implementation in Uzbekistan (1918-1930s) - Tulkin Mamanazarovich Togayev (International Journal on Integrated Education, 2023)
This article examines the approaches of Soviet leaders to the issue of the state language, the language policy of the Soviet state in the 1918-30s of the twentieth century, including the implementation of state policy on national languages in Uzbekistan. The content of decrees, resolutions and other legal documents of various levels adopted by the Communist Party and the Government of the Soviets on issues of equality of national languages, ensuring their development, office work in the state language, and indigenization of public administration is described. Also, the activities carried out in Uzbekistan on the basis of these official documents, the results achieved and changes in Soviet language policy are shown.